Acute Bronchitus: Causes, Simptoms, and Triatment with Home Remedies - Erkinjonovna, Sharapova Nozima (American Journal of Bioscience and Clinical Integrity, 2024)
Bronchitis is acute (sudden onset and temporary) or chronic (ongoing) inflammation of the bronchi.The bronchi are the large tubes that carry air from the trachea to the lungs. The inflammation triggers a cough that often produces mucus.